2020
DOI: 10.1021/acscombsci.0c00144
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Fmoc-Based Peptide Synthesis for DNA-Encoded Chemical Libraries: Reaction Conditions, Protecting Group Strategies, and Pitfalls

Abstract: Peptide drug discovery has shown a resurgence since 2000, bringing 28 non-insulin therapeutics to the market compared to 56 since its first peptide drug, insulin, in 1923. While the main method of discovery has been biological displayphage, mRNA, and ribosomethe synthetic limitations of biological systems has restricted the depth of exploration of peptide chemical space. In contrast, DNA-encoded chemistry offers the synergy of large numbers and ribosome-independent synthetic flexibility for the fast and deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…As a consequence, most of the conventional organic reactions are excluded from the toolbox of DEL chemistry. Researchers from academia and industry have since developed various DNA‐compatible reactions such as on‐DNA amide formation, [ 21 , 22 ] diazo‐transfer, [ 23 ] cross‐coupling reaction, [ 24 , 25 , 26 , 27 , 28 , 29 ] C‐H activation and functionalization, [ 30 , 31 , 32 , 33 , 34 , 35 ] ring‐closing metathesis, [ 36 , 37 ] Sulfur‐Fluoride Exchange (SuFEx) chemistry, [ 38 ] photo‐catalyzed reaction, [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and cycloaddition reactions. [ 46 , 47 , 48 , 49 , 50 ] Recently, the strategies of micellar‐mediated on‐DNA synthesis, [ 51 , 52 ] using chemically stabilized DNA barcodes, [ 53 ] solid support mediated on‐DNA synthesis, [ 54 ] and especially the reversible adsorption of DNA on solid supports have greatly expanded the on‐DNA synthetic toolbox.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, most of the conventional organic reactions are excluded from the toolbox of DEL chemistry. Researchers from academia and industry have since developed various DNA‐compatible reactions such as on‐DNA amide formation, [ 21 , 22 ] diazo‐transfer, [ 23 ] cross‐coupling reaction, [ 24 , 25 , 26 , 27 , 28 , 29 ] C‐H activation and functionalization, [ 30 , 31 , 32 , 33 , 34 , 35 ] ring‐closing metathesis, [ 36 , 37 ] Sulfur‐Fluoride Exchange (SuFEx) chemistry, [ 38 ] photo‐catalyzed reaction, [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and cycloaddition reactions. [ 46 , 47 , 48 , 49 , 50 ] Recently, the strategies of micellar‐mediated on‐DNA synthesis, [ 51 , 52 ] using chemically stabilized DNA barcodes, [ 53 ] solid support mediated on‐DNA synthesis, [ 54 ] and especially the reversible adsorption of DNA on solid supports have greatly expanded the on‐DNA synthetic toolbox.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction recovery rate was only 12%. We optimized the linker protecting group and deprotection conditions and found that the recoveries of the deprotection reaction of the Alloc protecting group, the Nvoc protecting group, and the Cbz protecting group could reach 99%, 88%, and 72%, respectively. In future designs, we can use suitable linkers and protecting groups to complete the construction of photo-cross-linking libraries under milder reaction conditions (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Young and coworkers reported a significant advancement in this field by constructing stapled peptides in DNA-encoded chemical libraries. [46,47] ALRN-5281 and ALRN-6924 are the two best clinical candidates synthesized by stapled peptide methodology.…”
Section: General Synthesis Strategy Of Stapled Peptidesmentioning
confidence: 99%